Aspects and issues of daylighting assessment: A review study. (December 2016) - Galatioto, A.; Beccali, M.
Abstract: Proper assessment of indoor daylighting conditions can significantly reduce energy consumption due to artificial lighting and can improve indoor visual comfort. This paper gives a critical review of the fundamental aspects of daylighting indices with the aim to provide a broad overview of methods and indices available to assess daylighting from varying points of view. Assessments cover distribution, availability over time and in specific climatic contexts, uniformity in the space, visual comfort issues and the relations between each of these aspects and a proper building and lighting design. A special focus on the assessment of indoor spatial and temporal uniformity is given. An analysis of the application of daylighting design by researchers and designers according to several area of interest is also presented.